The Conflict Between Day and Night in Anne Finch’s “A Nocturnal Reverie”: An Eco-critical Study - Sharif, Azad Hamad; Mohammad, Birzo Abdulkadir (Al-Adab Journal, 2019)
In this research the poem of Anne Finch, Countess of Winchelsea, “A Nocturnal Reverie” will be analyzed from an ecological perspective. Ann Finch’s contribution to understanding nature will be examined within ecocritical viewpoint and how her vision of nature is reflected in the poem. This study attempts to prove that Anne Finch was highly aware of the importance of nature in humans’ life and believed that humans are responsible for both nature and humans' welfare. With her poem Anne Finch tried to convince man that nature is a beautiful and living community that should be respected in order to reach inner harmony and to make the world a better, freer and kinder place. In the poem Finch represents nature as a united society, every part and aspect of which has its feelings, wishes and goals. Finch finds in natural society freedom and equality, but this is possible only at night. The day is the time of the “tyrant-man”, that belongs to a superior world and man suppresses the call of nature in himself. Still the tyranny of human cannot suppress nature completely because of the following reasons: a) man is not an authority, b) man feels the need in nature, and thus nature is superior to him.